Home Discharge following Critical Illness: A Qualitative Analysis of Family Caregiver Experience - Choi, JiYeon (Heart Lung, 2018)
BACKGROUND: Few studies have longitudinally explored the experience and needs of family caregivers of ICU survivors after patients’ home discharge. METHODS: Qualitative content analysis of interviews drawn from a parent study that followed family caregivers of adults ICU survivors for 4 months post-ICU discharge. RESULTS: Family caregivers (n=20, all white, 80% woman) viewed home discharge as positive progress, but reported having insufficient time to transition from family visitor to the active caregiver role. Caregivers expressed feelings of relief during the steady recovery of family members’ physical and cognitive function. However, the slow pace of improvement conflicted with their expectations. Even after patients achieved independent physical function, emotional needs persisted and these issues contributed to caregivers’ anxiety, worry, and view that recovery was incomplete. CONCLUSION: Family caregivers of ICU survivors need information and skills to help managing patients’ care needs, pacing expectations with actual patients’ progress, and caregivers’ health needs.